Penerapan Sanksi Administratif Bagi Badan Usaha Yang Tidak Ikut Serta Dalam Kepersertaan BPJS Kesehatan Menurut Peraturan Nomor 86 Tahun 2013 - Montana, Riko; Phahlevy, Rifqy Ridlo (Indonesian Journal Publisher, 2024)
This study analyzes whether the application of administrative sanctions for business entities that do not participate in the health BPJS has been fulfilled properly or not, using the Socio Legal research method and the Sociological Juridical approach, the results are obtained in a condition that is actually in the field that there is still a lack of understanding of rights and obligations. This causes many business entities to be negligent of the rights and obligations of their employees. The conclusion that can be drawn in the application of administrative sanctions in general in its application to BPJS Kesehatan Sidoarjo business entities (employers) only reaches the stage of written reprimand and mostly after receiving written warnings 2 (two) times, the business entities immediately register their workers as PPU participants. (Wage Recipient Employee).